Contrastive Markers in Contrast - Maria Josep Cuenca; Sorina Postolea; Jacqueline Visconti (Discours)
Contrastive markers are one of the richest groups of discourse markers in Romance languages. There are several conjunctions and other connectives that can express various types of contrast both at the text level and at the sentence level. In this paper, the main contrastive markers of Spanish, Catalan, Italian and Romanian will be classified and compared as for form, lexical base (or source) and meaning, with the aim of providing a cross-linguistic description of the way in which this class of discourse relations is signaled in these four different Romance languages. Two general meanings will be considered, namely, non-exclusive contrast (including weak contrast, opposition, concessive opposition, and conditional opposition) and exclusive contrast. Our analysis reveals similarities across languages, which go back to common origins, as well as important differences, derived from the fact that each language has developed a paradigmatic system that shows interesting divergences in use.